PERTANGGUNGJAWABAN PIDANA KORPORASI (PT) ATAS TINDAK PIDANA PERUSAKAN LINGKUNGAN HIDUP - Erni Juniria Harefa; Pondang Hasibuan; Sahat Benny Risman Girsang; Herlina Manullang (Magister Hukum Universitas HKBP Nommensen, 2021)
The occurrence of environmental crimes in the form of environmental pollution and/or destruction, mostly carried out in the context of running an economic business, and is also the attitude of the authorities and entrepreneurs who do not carry out or neglect their obligations in environmental management. Environmental pollution and/or destruction continues to increase in line with the increase in industrial activities or the like, of course the environment needs legal protection. Article 116 of the Environmental Protection and Management Law (UUPPLH), makes the concept of corporate criminal responsibility and corporate management (directors, managerswho are responsible for managing the company's environment, can even be asked to shareholders and commissioners) together, in the event that the activities and/or business of the corporation cause environmental pollution and/or destruction. On the other hand, the accountability of the directors/management of the corporation is also needed because there is a possibility that the sanctions imposed on the corporation will not affect the lives of the leaders/management of the corporation.The method used in this thesis research is normative juridical research using primary, secondary, and tertiary legal materials. This study uses library research techniques, which are then analyzed qualitatively. Based on the results of the study, that corporate criminal liability in Article 116 paragraph (1) UUPPLH is based on the identification of Theory and Vicarious Liability. Meanwhile, the director's criminal responsibility as an individual for criminal acts of environmental destruction occurs as long as the director has the authority to prevent violations or to improve the situation. Meanwhile, the criminal responsibility of the director representing the PT organ for environmental crimes can be identified based on the Responsible Corporate Officer Doctrine (RCO) and Strict Liability, because his position in the company has an obligation to take action to ensure that the violation will not occur as stipulated in Article 116 and 117 UUPPLH.